The use of rotating cylinder electrode to study the effect of 1,3-dihydroxypropane on copper electrorefining - Soliman,H.M.A. (2006)
The effect of different concentrations of 1,3-dihydroxypropane (DHP) on the electrodeposition of copper powder from acidified copper sulphate solution has been studied at different temperatures and different speeds of rotation. Copper powder was electrodeposited onto rotating cylinder electrode (RCE) that made of pure copper. The inhibition percentage, P, in the electrodeposited copper powder was 0.00 - 92.91%, depending on the experimental variables. P was affected by temperature and mole fraction of DHP, while rotation did not show any influence whatsoever. Values of the activation energy of electrodeposition process, Ea, were found to be less than 28 k J mol-1 indicating diffusion controlled process. The overall mass transfer correlations under the present conditions have been obtained using the dimensional analysis method. The data were valid for 80 < Sh (Sh = Sherwood number) < 3970, 290 < Sc (Sc = Schmidt number) < 59284 and 271 < Re (Re = Reynolds number) < 52705 and the results agreed with the previous studies of mass transfer to rotating cylinders in turbulent flow regimes. Experimental determination of the solution critical velocity was obtained for blank and 20% (v/v) DHP solutions at 298 K. The effect of time, DHP content, temperature and the speed of rotation on the morphological changes of the electrodeposited copper powder as well as deposits composition and particle size have been studied. Various particle sizes ranged 60.5 - 203.4 nm were obtained, characterized by EDS and XRD and found to be pure copper with small amount of oxygen. Different topographs proved that the rate of copper electrodeposition increased by increasing time, temperature and the speed of rotation. In addition, they proved that the deposition rate decreased by adding DHP to the solution. Therefore, the results obtained by SEM supported those results obtained by electrochemical measurements. The morphological structure of deposited copper powder from 20% (v/v) DHP at 1000 rpm and 298 K was unique, rounded-crystalline aggregates with voids.